THE INFLUENCE OF INTRA-FAMILY COMMUNICATION ON HIGH SCHOOL STUDENTS’ PERCEPTIONS OF FAMILY LIFE AND ITS PSYCHOLOGICAL MECHANISMS (Bulletin of Innovative Research, 2026)
This article analyzes, from a psychological perspective, the process of forming high school students’ perceptions of family life and the influence of intra-family communication on this process. The theoretical foundation of the study is based on social learning theory, attachment theory, psychosocial development theory, and the sociocultural approach. The results of the empirical research demonstrate that open and supportive communication within the family plays a significant role in shaping students’ positive and responsible attitudes toward their future family life. Conversely, conflictual or emotionally distant relationships contribute to the development of uncertain or negative perceptions of family values among adolescents. The findings of the study are important for developing practical recommendations for parents and educators in preparing young people for family life.